Complications and side effects of Wide-Awake Local Anaesthesia No Tourniquet (WALANT) in upper limb surgery: a systematic review and meta-analysis - Jad Lawand (21633647) (2024)
Purpose Wide-Awake Local Anaesthesia No Tourniquet (WALANT), a groundbreaking anaesthetic technique resurging in practice, warrants a comprehensive safety analysis for informed adoption. Our study aimed to identify complications/side effects of WALANT upper limb procedures through a systematic review and meta-analysis. Methods This PROSPERO-registered study was performed with strict adherence to PRISMA guidelines. Embase, OVIDMedline, Cochrane, Web of Science, and Scopus databases were searched until February 2023. Inclusion criteria involved English articles, reporting complications/side effects in primary WALANT upper limb surgeries. Outcomes included all complications and side effects, data on the anaesthetic mixture, publication year/location, study type, and procedures performed. The meta-analysis employed the Freeman-Tukey Double Arcsine Transformation, computed I2 statistics, and utilized common or random effects models for pooled analysis. Results 2002 studies were identified; 79 studies met the inclusion criteria representing 15,595 WALANT patients. A total of 301 patients had complications, and the meta-analysis using a random effects model provided a complication rate of 1.7% (95% CI: 0.93–2.7%). The most reported complications were superficial infection (41%, n = 123/300), other/specified (12%, n = 37/300), and recurrent disease (6.7%, n = 20/300). A decade-by-decade analysis revealed no statistically significant difference in complication rates spanning the last three decades (p = 0.42). Adding sodium bicarbonate to the anaesthetic solution significantly reduced postoperative complications (p = 0.025). Conclusion WALANT has a low overall complication rate of 1.7%, with no significant temporal variation and a significant reduction in complications when sodium bicarbonate is added to the anaesthetic solution. Our findings support the safety of WALANT in upper limb procedures. Other Information Published in: International Orthopaedics License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00264-024-06104-9